Analytical Review of the Impact of Augmented Reality on the Structure of Graphic Design in Ukrainian and Foreign Projects - Krutova, Oksana (HUDPROM: The Ukrainian Art and Design Journal, 2024)
The article provides an analytical review of the impact of augmented reality (AR) technologies on the structure of graphic design in both Ukrainian and international contexts. The modern application of AR in graphic design significantly expands the user interaction with visual product, enabling the creation of interactive and three-dimensional solutions. Special attention is given to structural transformations in traditional graphic design, including new approaches to composition, typography, color schemes, and textures that adapt to the specifics of three-dimensional environments. The study reveals that AR integration alters not only design aesthetics but also functionality, placing greater emphasis on user interaction. A key issue explored is the adaptation of UX/UI design to AR, ensuring intuitive and seamless navigation within three-dimensional spaces. Ukrainian AR projects frequently incorporate national identity, integrating cultural elements to preserve heritage and foster interest in national art. In contrast, Western AR projects often focus on commercial applications, particularly in marketing, gaming, and entertainment industries. The article also discusses technical limitations that hinder the widespread adoption of AR, such as the need for high-performance GPUs and optimization challenges for low-power devices. The conclusions highlight prospects for further research in this field, particularly the development of cost-effective AR solutions for mass markets and broader adaptation of AR technologies for both commercial and cultural projects. The study underscores the importance of AR as a tool for expanding the possibilities of graphic design amid rapid technological advancements. At the same time, it emphasizes the need to balance innovation with practicality, addressing UX/UI adaptation challenges and overcoming technical constraints to optimize AR content for diverse user needs.